Evaluation of the synergistic effect of yeast and Chicory-inulin on rumen fermentation parameters and estimation of methane emission - Bett Kipkorir, Josphat; Migwi, Perminus K.; Ondiek, James O. (Acta Agraria Debreceniensis, 2024)
Probiotics and prebiotics are feed additives that have been extensively utilised in animal nutrition for a considerable duration. However, only some studies have investigated their synergistic effects on rumen fermentation parameters and their role in minimizing methane emission. Therefore, this study examined the impact of combining chicory-inulin with yeast (Saccharomyces cerevisiae) on rumen fermentation parameters and methane emissions in weaned dairy goats. The feeds were formulated into eight diets and offered to 24 Saanen×Toggenburg crossbred weaned female dairy goats weighing 14±0.5 Kg in a Completely Randomized Design with a (4x2) factorial arrangement. The diets were Rhodes grass hay and chicory supplementation at four levels: 0, 10, 20, 20, and 30% as the main effects and with (+) and without yeast (-) yeast as interaction levels. The findings indicated that the inclusion of yeast and Chicory had a significant effect (p<0.05) on rumen pH, ammonia nitrogen concentrations, production of volatile fatty acids), and estimated methane emission. The highest pH was recorded in T1- with 7.27. It was followed closely by T1+ with 6.73. T1+ recorded the highest methane (39.67 mmol/L), while T4- had the lowest (32.42 mmol/L). This study concludes that Chicory-inulin has prebiotic properties by maintaining pH levels and affecting amounts of ammonia nitrogen. The lack of a significant interaction effect between yeast and Chicory in methane emission implies that their combined influence may not significantly affect methane emissions in the current study’s experimental settings.